A high-performance anode for lithium ion batteries: Fe₃O₄ microspheres encapsulated in hollow graphene shells - Jiang, Yu; Jiang, Zhong-Jie; Yang, Lufeng; Cheng, Shuang; Liu, M (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
The encapsulation of transition metal oxide (TMO) particles in a graphene hollow shell to form a core-void-shell structure is an attractive way to improve the electrochemical performance of TMO-based electrodes for lithium ion batteries (LIBs). First, the continuous graphene shell may enhance the electrical conductivity of the electrodes and thus facilitate current collection and charge transfer associated with lithium storage. Second, the unique shell structure may suppress the aggregation of the core TMO particles while the void space between the core and shell may accommodate the large volume changes of the core during charge–discharge cycling, which enhances electrode stability against cycling. Third, the high specific surface area may improve the accessibility of active electrode materials to the electrolyte, which could effectively reduce the solid-state diffusion length and thus enhance Li ion transport and rate capability. When tested in a LIB, a Fe₃O₄@rGO composite electrode exhibits an initial reversible capacity of 1236.6 mA h g⁻¹, which is much higher than that of an electrode based on bare Fe₃O₄, a physical mixture of Fe₃O₄ and graphene, or other forms of Fe₃O₄ reported in the literature. In addition, the cycling performance and rate capacity are also much better. The results clearly demonstrate that this unique electrode architecture is ideally suited for LIBs and other electrochemical energy storage and conversion devices.